Energy balance in a bioenergy plantation of Populus deltoides clone Lux in a site with Mediterranean environment - Cabrera, Antonio; Tozzini, Cristiano; Espinoza, Sergio; Santelices, Rómulo; Bonari, Enrico (Bosque (Valdivia), 2017)
Given the energy challenges confronted by the world in general, where Chile is not an exception, forest energy crops have been positioned as a viable alternative to diversify this country's energy matrix. These types of crops, still under development, are based on short rotation shifts with high biomass production. The problem arises when assessing the sustainability of such crops. Accordingly, the energy balance is an important factor to assess sustainability i.e. we cannot spend more energy to produce biomass than what is released by the biomass combustion. This work presents the energy balance of harvest products at roadside in a Populus deltoides clone Lux short rotation forestry during eight years (2000-2008), comparing biennial (T2) and triennial (T3) shifts. Consequently, we calculated the energy cost of production and harvest and the amount of energy released in the combustion of the biomass generated. Both rotation shifts got positive results, being triennial shifts more energy efficient than biennial ones (34.7 T2 vs 25 T3).